Pyrazolyl Benzamides: Synthesis, Characterization and Potent Biological Activity, Part-2 - Ganesh, Akula; Bikshapathi, Darna; Kulkarni, Ravindra (Current Enzyme Inhibition, 2018)
Background: A range of biological activities including anti-inflammatory, antiangiogenic, antitubercular and kinase inhibitory activity have been reported for pyrazole derivatives. Serious medicinal chemistry approaches for the development of effective antibacterial agents have resulted in only few new compounds with the lack of activity against a wide range of microbes. In continuation with our quest for developing anti-inflammatory and antimicrobial agents bearing pyrazole scaffold, a series of N-pyrazolylbenzamides 1-22 were synthesized. Methods: All the desired compounds have been synthesized by following reported chemical reactions and upon confirmation of structure of compounds through spectral data, all the compounds were screened for antibacterial including resistant strains, antifungal, antitubercular activity and antiinflammatory activity. Results: In the antibacterial activity screening four compounds exhibited potent antibacterial activity and admirable antifungal activity. Compounds 7 and 17 demonstrated potent activity with MIC of 3.12 μg/mL against Bacillus subtilis and compounds 3 and 17 were found to be highly potent against some of resistant strains with MIC value of 3.12 μg/mL. Compounds 5 and 17 showed antitubercular activity with MIC value of 6.25 μg/mL. All the compounds were also subjected for anti-inflammatory activity at 50 mg/Kg dose, three compounds 8, 12 and 16 produced significant anti-inflammatory activity over 50% in the third hour of observation. Conclusion: Structurally characterized compounds have been screened for anti-inflammatory and antimicrobial activities. Compounds 7 and 17 were found to be potent antibacterial compounds and 17 emerged out as one of the potent compounds with activity against MRSA, VRSA and E. faecium and 5 and 17 showed MIC value of 6.25 μg/mL against H37Rv mycobacterial strain. Compounds 4, 7, 8, 12 and 16 exhibited anti-inflammatory activity.
Keywords: anti-inflammatory